Impact of Post-Harvest Biomass Burning on Aerosol Characteristics and Radiative Forcing over Patiala, North-West region of India - Sharma, Deepti; Singh, Manjit; Singh, Darshan (Journal of the Institute of Engineering, 2012)
The present study deals with impact of post-harvest biomass burning on aerosol characteristics over Patiala (Lat: 30.33°N; Long: 76.4°E), Punjab state, India during 2008-09, using ground based and satellite data. Results of Aerosol Optical Depth (AOD) measurements using MICROTOPS II show significant variations with highest AOD500 ≈2.65 in October 2008 and ≈1.71 in November 2009. The maximum monthly mean values of angstrom parameters “α” and “β” are 1.13±0.16 and 0.39±0.20, respectively. Daily averaged values of Black Carbon (BC) mass concentration during day time show significant variations (8-18μg/m³) yielding SSA varying from 0.76-0.88 during highly turbid days and 0.95-0.97 during less turbid days. During highly turbid days, the estimated atmospheric radiative forcing using SBDART varies from +43.0 to +86.5Wm-2 suggesting high BC concentration in the atmosphere associated with paddy residue burning in the fields. DOI: http://dx.doi.org/10.3126/jie.v8i3.5927 JIE 2011; 8(3): 11-24